HUBUNGAN PENGETAHUAN GIZI DAN KEBIASAAN MAKAN DENGAN BERAT BADAN SANTRIWATI DI PONDOK PESANTREN AMANATUL UMMAH SURABAYA - Dewi Putri Kurniawati; Wesiana Heris Santy; Pratiwi Hariyani Putri (UNUSA Press, 2019)
The nutrition problems that often occur in adolescence are multiple nutritional problems that is overweight and thin. It’s happen because imbalace between energy consumption and expulsion energy in the body metabolism. The prevalence of overweight and thin teenagers aged 16 – 18 are rising each year. The purpose of this research is to know the relation of nutrition knowledge and eating habits with weight of santriwati in boarding school Amanatul Ummah Surabaya. The design of this research is the cross sectional. The sample of research is 45 respondents, taken using a proportional random sampling. The instrument using a questionnaire, data analysis using spearman rank test with significance level 0.05. The research shows that almost half of the repondent having overweight (31.1%) and a small part has skinny (11.1%). The results of the test of rank spearman shows there is unrelation between nutrition knowledge with weight (p = 0,205) and there is relation between eating habits with weight (p = 0.000). It can be concluded that nutritional knowledge does not affect a person to choose nutritious foods and according to the need, but eating habits will effect for weight. Teenagers should apply of nutrition knowledge that they have so can change eating habits.